Adobe Photoshop CC for photographers a professional image editor's guide to the creative use of Photoshop for the Macintosh and PC - Evening, Martin (Routledge, 2018)
Adobe Photoshop CC for Photographers by acclaimed digital imaging professional Martin Evening has been revamped to include detailed instruction for all of the updates to Photoshop CC on Adobes Creative Cloud, including significant new features, such as the painting tool and Pen path tool refinements and Range Masking in Camera Raw. This guide covers all the tools and techniques photographers and professional image editors need to know when using Photoshop, from workflow guidance to core skills to advanced techniques for professional results. Using clear, succinct instruction and real world examples, this guide is the essential reference for Photoshop users. The accompanying website has been updated with new sample images, tutorial videos, and bonus chapters.